Mekanisme Pencegahan Fraud dalam Peningkatan Kinerja Organisasi - Gunawan, Mochamad Rizqi; Rachmawati, Rima (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2023)
This research was conducted as an effort to explore the determinants of company performance by considering the variables of the whistleblowing system, organizational commitment and fraud prevention. More specifically, researchers tested the direct influence of the whistleblowing system and organizational commitment on fraud prevention. Researchers also looked at the influence of fraud prevention on company performance. Then, researchers looked at the mediating role of fraud prevention. This research was conducted at health service providers in the city of Tasikmalaya, which includes hospitals and health centers, with a total sample of 70 institutions. This research data was distributed through a survey system, then processed using Structural Equation Modeling using Partial Least Square (SEM-PLS). The results of this research show that the whistleblowing system and organizational commitment have a positive effect on fraud prevention, while fraud prevention has a positive effect on company performance. Finally, researchers confirm the mediating role of fraud prevention in the influence of the whistleblowing system and organizational commitment on company performance.